2016
DOI: 10.5935/0103-5053.20160024
|View full text |Cite
|
Sign up to set email alerts
|

Strategy of Sample Preparation for Arsenic Determination in Mineral Fertilizers

Abstract: A method for determination of arsenic in mineral fertilizers by continuous flow hydride generation atomic absorption spectrometry (CF-HG-AAS) was developed by using diluted acid and digester block with perfluoroalkoxy (PFA) tubes to sample preparation. An additional sample preparation procedure using microwave-assisted digestion was evaluated and compared with the proposed procedure. A full factorial design was applied to investigate the effect of the variables and the best conditions found were 7 mol L −1 HNO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
0
4
0
4
Order By: Relevance
“…One reason for the successful determination by HG-MIP OES with N 2 gas is the use of KI as reductant and a masking agent to decrease matrix effects caused by transition metals, which can compete with the analyte in the reaction with NaBH 4 to form volatile species. Several authors ,, have demonstrated the role of KI as reductant and masking agent in the prereduction step when working with HG. Another reason for reaching accurate results by HG-MIP OES N 2 plasma was the careful selection of wavelengths, mainly for the analysis of samples with high concentrations of transitions metals.…”
Section: Resultsmentioning
confidence: 99%
“…One reason for the successful determination by HG-MIP OES with N 2 gas is the use of KI as reductant and a masking agent to decrease matrix effects caused by transition metals, which can compete with the analyte in the reaction with NaBH 4 to form volatile species. Several authors ,, have demonstrated the role of KI as reductant and masking agent in the prereduction step when working with HG. Another reason for reaching accurate results by HG-MIP OES N 2 plasma was the careful selection of wavelengths, mainly for the analysis of samples with high concentrations of transitions metals.…”
Section: Resultsmentioning
confidence: 99%
“…Ferramentas quimiométricas têm sido utilizadas para a otimização de programas de aquecimento e reagentes em procedimentos de preparo de amostras (Kokot et al, 1992;Macedo et al, 2009;De Jesus et al, 2013;Machado, Pereira-Filho, et al, 2016). Neste trabalho, devido ao grande número de resultados a serem considerados, a Análise de Componentes Principais (PCA, Principal Components Analysis) foi aplicada para facilitar a escolha do melhor procedimento de digestão.…”
Section: Análise De Componentes Principais (Pca)unclassified
“…O aquecimento por micro-ondas em frascos fechados é um modo de obter altas temperaturas em um curto espaço de tempo (Kane et al, 2006;Mackey et al, 2007;Shirisha et al, 2014;Webb et al, 2014), que melhora a eficiência da digestão e possibilita o uso de ácidos diluídos. O ácido nítrico diluído combinado com peróxido de hidrogênio na digestão assistida por radiação microondas foi também proposto para as determinações de As (Machado, Pereira-Filho, et al, 2016;Machado, Virgilio, et al, 2016) e B, P e S (Oliveira et al, 2016) (Bizzi et al, 2014). Além disso, o uso de ácido diluído para a decomposição da amostra é uma boa estratégia para minimizar o consumo de reagentes, geração de resíduos e valores dos brancos analíticos (Nóbrega et al, 2012;Bizzi et al, 2014;Machado, Pereira-Filho, et al, 2016;Machado, Virgilio, et al, 2016;Oliveira et al, 2016).…”
Section: Introductionunclassified
See 2 more Smart Citations